Herniated Nucleus Pulposus in Dr. Hasan Sadikin General Hospital Bandung Indonesia - Annisa Ikhsanawati; Bambang Tiksnadi; Arifin Soenggono; Nucki Nursjamsi Hidajat (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Herniated nucleus pulposus (HNP) is one of the most common diseases of the spine. For an optimal management and prevention, there’s a need for data on factors related to the onset of complaints because this disease lowers the quality of life and increases morbidity. This study is aimed to see the scale and pattern of the HNP in Dr. Hasan Sadikin General Hospital, Bandung.Methods: This is a descriptive study with the design of case series, data was obtained from medical records of patients with the diagnosis of HNP in the inpatient care of Dr. Hasan Sadikin General Hospital in the period of 2007–2011.Results: According to the study on 79 patients, with 43 men and 36 women, the highest incidence was at the age group of 51–60 years old (31.6%) and most common occupation was civil servant (11.4%). The most common clinical symptoms were sciatica (51.9%) and low back pain (51.9%). Most frequent location was in the lumbar vertebrae at the level of L5–S1 (58.2%). Trauma was found to be the highest relatable history in the patients (39.2%). Therapy of choice was primarily conservative (58.2%) and most patients went home after the progression (84.8%). The year 2007 showed the highest prevalence of HNP at 25.3%. The most common clinical symptoms were sciatica (51.9%) and low back pain (51.9%)Conclusions: The most common clinical symptoms were sciatica and low back pain. Most frequent location was in the lumbar vertebrae at the level L5–S1. [AMJ.2015;2(1):179–85]